Effect of integrated nutrient management in boro rice cultivation (SAARC Journal of Agriculture, 2016)
An experiment was carried out in the farmers field of village Boira under Kotoali Thana, District-Mymensingh in Boro season (Jannuary to May 2013) to find out the effect of integrated nutrient management in Boro rice cv. BRRI dhan29 cultivation. The experiment consisted of the following treatments- control (no manure and no fertilizer) (T1), recommended dose of prilled urea and PKSZn (T2), 50% of the recommended dose of prilled urea and PKSZn + cowdung 5 t ha-1 (T3), 50% of recommended dose of prilled urea and PKSZn + poultry manure 2.5 t ha-1(T4), 50% of recommended dose of prilled urea and PKSZn + cowdung 10 t ha-1 (T5), 50% of recommended dose of prilled urea and PKSZn + poultry manure 5 t ha-1 (T6), cowdung 10 t ha-1 (T7), poultry manure 5 t ha-1 (T8), full dose of USG (2.7g) + recommended dose of PKSZn (T9), full dose of USG (2.7g) + cowdung 10 t ha-1 (T10), full dose of USG (2.7g) + poultry manure 5 t ha-1 (T11), full dose of USG (2.7g) + cowdung 5 t ha-1 (T12), full dose of USG (2.7g) + poultry manure 2.5 t ha-1(T13), USG (1.8g) + poultry manure 5 t ha-1 (T14), USG (1.8g) + poultry manure 2.5 t ha-1 (T15) and farmers practice (Urea 250 kg ha-1, TSP 220 kg ha-1, MoP 130 kg ha-1, gypsum 130 kg ha-1) (T16). The experiment was laid out in a randomized complete block design with three replications. Results of the experiment showed that integrated nutrient management had significant effect on yield contributing characters and yield of BRRI dhan29. The tallest plant (93.33 cm) was found in T2 treatment (recommended dose of prilled urea and PKSZn), the highest number of total tillers hill-1(16.85) and effective tillers hill-1 (15.90) were obtained in T11 treatment (USG (2.7g) + poultry manure 5 t ha-1). The highest 1000-grain weight (22.40g), grain yield (7.19 t ha-1) and straw yield (8.08 t ha-1) were recorded in T10 treatment (full dose of USG (2.7g) + cowdung 10 t ha-1) and the lowest grain yield (4.43 t ha-1) and straw yield (5.21 t ha-1) were obtained in T7 treatment (cowdung 10 t ha-1). From the study, it can be concluded that inorganic fertilizer along with manure greatly influence the yield contributing characters and yield of Boro rice and full dose of USG (2.7g) with cowdung (10 t ha-1) appears as the promising combination for Boro rice (cv. BRRI dhan29) cultivation.SAARC J. Agri., 13(2): 131-140 (2015)